Bibelkommentarer i undervisning: Ett mångfaldigt men inte enfaldigt perspektiv - Nyström, Jennifer (Svensk exegetisk årsbok, 2025)
This joint article, comprising five contributions, results from a workshop focused on the use of Bible commentaries in teaching at Swedish universities today. While each contribution presents a distinct style and voice, we all agree on the importance of learning how to use commentaries in higher education and, equally, the need for their active application. We also all welcome the development of more commentaries in Swedish. The first two contributions come from professors - one specializing in New Testament studies and the other in Hebrew Bible - who reflect on the practical use of commentaries in teaching and how this should or should not be approached. The following three shorter contributions focus on Bible commentaries in Swedish: what they are, how they are used, and why they are needed. One calls for the creation of Swedish commentaries for the Hebrew Bible, another surveys the field of commentaries on the New Testament, and the last provides a perspective from practical theology, emphasizing the need for commentaries accessible to laypeople.